Analisis de plan de negocio para el proceso de exportación de hierbas aromáticas - Villamil Molina, Maria Fernanda (Universidad Antonio Nariño, 2022)
In the present investigation, the search for a target market that allows the international commercialization of dehydrated aromatic herbs was carried out, in this way it intends to evaluate and formulate strategies that allow the export process to be carried out, having an analysis of the market, as well as the main consumers and producers of aromatic herbs worldwide, showing us the research that the United States is the most convenient foreign market, as it is one of the largest buyers of aromatic plants that the country has and to be successful, all tariff requirements must be met and not tariff established by the US government. The parameters for the commercialization are evaluated where the logistics are detailed, and the feasibility that this may have is evaluated. Finally, the approach of the conclusions and recommendations that serve as a basis to have a detailed vision of what can be obtained with this type of projects is made.